(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Ayurvedic dosage forms are mostly poly herbal, which is more effective compared to the single herb therapies. Nayopayam kwatha (NK) is a widely prescribed polyherbal formulation for postnatal care, heart diseases and respiratory ailments. It is quoted in Ayurvedic textbooks viz; Vaidya Manorama and Arogyaraksha Kalpadruma. The formulation consists of Bala, Jeeraka and Nagara. The source plants are Bala (Sida cordifolia Linn as per AFI and Sida retusa Linn in Kerala), Jeeraka (Cuminum cyminum Linn) and Nagara (Zingiber officinale Rosc). A detailed literature review is conducted on NK to explore its probable mode of action in respiratory ailments. Pharmacological actions of each ingredients and proven pharmacological activities are included in this study. Ethno botanical variability is noticed in NK manufactured by different pharmaceutical agencies. Apart from this, it is having Ushna veerya, predominantly Katu rasa and Vatakaphaharatwa which in turn act against the respiratory ailments. Considering these all aspects, NK is a potent formulation used for respiratory infections and inflammations.